Pengaruh Pengumuman Paket Kebijakan Ekonomi Jilid XIV Terhadap Abnormal Return Seluruh Saham di Bursa Efek Indonesia - JUANDY GERRY EDAM; Joanne V. Mangindaan; Henny S. Tarore (Universitas Sam Ratulangi, 2017)
The purpose of this study is to determine the reaction of the capital market to an eventor announcement in this case is the announcement of the Economic Policy Package VolumeXIV on November 10, 2016. Capital market reaction will be seen or observed throughindicators of abnormal return of listed companies shares in Indonesia Stock Exchange.Researchers believe that one of the factors that cause changes or fluctuations in stock pricesis the information in circulation. Such as regulations or policies issued to encourageeconomic growth that are believed to add value to the firm. This research uses event studymethod. Sampling technique using nonprobabilitas method in the form of purposivesampling. The samples used in this research are 45 stocks of companies that are included inthe LQ45 index component for the period of August 2016 - January 2017. The observationperiod in this research is 71 trading days consisting of 60 days in the estimated period, 11days in the event period divided into five days before and five days after the date of the event.The statistical test in this research uses parametric statistics in the form of one sample t-testand paired sample t-test. Based on the results of different test with one sample t-test showsthat there is a positive significant average abnormal return that occurs around theannouncement of Economic Policy Volume XIV, but average abnormal return positive issignificant only occurs at the time of policy announcement (t0). The result of different test ofpaired sample t-test shows that there is no significant difference between the averageabnormal return before and after the announcement of Economic Policy Package VolumeXIV. After conducting the research, it can be concluded that there is a positive marketreaction to the announcement of the Economic Policy Package Volume XIV.Keywords : Event Study, Abnormal Return, Economic Policy Package Volume XIV.